Identifikasi Kupu-Kupu Di Taman Hutan Raya Ir. H. Djuanda Jawa Barat - Dicky; Nur Aziema; Nabila Erma (Pro-Life, 2024)
Identification of butterflies in the Grand Forest Park Ir. H. Djuanda performed on November 2022 to August 2023. The aim of this research is to determine the butterfly species found in the Tahura Ir.. H. Juanda. The research is a descriptive qualitative study which uses field observation methods with exploratory survey techniques (surveys) and literature studies. Butterflies are identified based on their morphological characters using Kupu-Kupu (Lepidoptera: RHOPALOCERA) di Sumatera books, iNaturalist application, and other literary sources. There are 117 species of butterflies from 71 genera and 5 families spread across this area. Butterfly species from the Nymphalidae family dominate this area, while the fewest butterfly species come from the Hesperiidae and Papilionidae family. Butterflies can be used as a bioindicator of a good forest and environmental because they are sensitive to environmental damage.